(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
The rapid growth of electric vehicles (EVs) has created a strong demand for efficient and convenient charging solutions. Conventional charging methods require vehicles to stop for long durations, reducing usability and increasing travel time. This limitation highlights the need for innovative approaches that can improve the practicality and adoption of EV technology. This paper presents the design and implementation of a wireless on-road charging system that enables electric vehicles to charge dynamically while in motion. The system is based on electromagnetic induction, where transmitter coils embedded beneath the road generate a magnetic field, and receiver coils mounted on the vehicle capture this energy and convert it into electrical power. The received power is rectified, regulated, and used to charge the vehicle battery efficiently. An embedded controller monitors and controls the charging process, while a display unit provides real-time system information. This approach reduces dependency on stationary charging stations, minimizes charging time, and improves driving range, thereby reducing range anxiety. A prototype model is developed to validate the feasibility of wireless power transfer for moving vehicles. The system also considers proper coil alignment, safety, and reliability to enhance performance. The results demonstrate that the proposed system supports continuous charging and contributes to the development of smart roads and sustainable transportation infrastructure, making it a promising solution for future electric mobility